2018
DOI: 10.1002/pits.22126
|View full text |Cite
|
Sign up to set email alerts
|

Parent and teacher satisfaction with school‐based psychological reports

Abstract: School psychologists spend a great deal of time translating assessment results into a psychoeducational report. The importance of creating reports that are both useful and understandable to the readers of the report while also being efficient for the school psychologist cannot be overstated. This study examines parent and teacher perceptions regarding the quality, understandability, and usefulness of school‐based psychological reports. Results of the surveys indicate that both parents and teachers perceive psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 22 publications
0
41
0
4
Order By: Relevance
“…Rahill () examined teachers’ perceptions of quality, understandability, and usefulness of psychological reports. Teachers perceive psychological reports as focusing on tests and test scores as opposed to descriptive and individualized information that helps in recommendations and intervention planning.…”
Section: Included Studies’ Results Discussion and Research Recommenmentioning
confidence: 99%
See 4 more Smart Citations
“…Rahill () examined teachers’ perceptions of quality, understandability, and usefulness of psychological reports. Teachers perceive psychological reports as focusing on tests and test scores as opposed to descriptive and individualized information that helps in recommendations and intervention planning.…”
Section: Included Studies’ Results Discussion and Research Recommenmentioning
confidence: 99%
“…While most research found reports written with less jargon to be rated as more useful and comprehensible (Wiese et al, ), some research found no effect or reports with heavy jargon to be rated as more useful, professional, and understandable (Andrews & Gutkin, ; Fletcher et al, ; Raforth & Richmond, ). One study found teachers were dissatisfied with the high degree of technical jargon used in psychological reports (Rahill, ). A second study found teachers found little utility in reports with heavy jargon and to be more numbers/scores focused without the student in mind (Pelco et al, ).…”
Section: Included Studies’ Results Discussion and Research Recommenmentioning
confidence: 99%
See 3 more Smart Citations